The functional potential and active populations of the pit mud microbiome for the production of Chinese strong‐flavour liquor - Tao, Yong (Microb Biotechnol, 2017)
The popular distilled Chinese strong‐flavour liquor (CSFL) is produced by solid fermentation in the ground pit. Microbes inhabiting in the pit mud (PM) on the walls of the fermentation pit are responsible for the production of caproic acid (CA) that determines the quality of CSFL to a large degree. However, little is known about the active microbial populations and metabolic potential of the PM microbiome. Here, we investigated the overall metabolic features of the PM microbiome and its active microbial components by combining metagenomics and MiSeq‐sequencing analyses of the 16S rRNA genes from DNA and RNA (cDNA). Results showed that prokaryotes were predominant populations in the PM microbiome, accounting for 95.3% of total metagenomic reads, while eukaryotic abundance was only 1.8%. The dominant prokaryotic phyla were Firmicutes, Euryarchaeota, Bacteroidetes, Actinobacteria and Proteobacteria, accounting for 48.0%, 19.0%, 13.5%, 2.5% and 2.1% of total metagenomic reads respectively. Most genes encoding putative metabolic pathways responsible for the putative CA production via chain elongation pathway were detected. This indicated that the PM microbiome owned functional potential for synthesizing CA from ethanol or lactate. Some key genes encoding enzymes involved in hydrogenotrophic and acetoclastic methanogenesis pathways were detected in the PM metagenome, suggesting the possible occurrence of interspecies hydrogen transfer between CA‐producing bacteria and methanogens. The 16S rDNA and 16S rRNA profiles showed that the Clostridial cluster IV, Lactobacillus, Caloramator, Clostridium, Sedimentibacter, Bacteroides and Porphyromonas were active populations in situ, in which Clostridial cluster IV and Clostridium were likely involved in the CA production. This study improved our understandings on the active populations and metabolic pathways of the PM microbiome involved in the CA synthesis in the CSFL fermentation.